Set the argument of the logarithm equal to zero.

Solve for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>12</mn></mstyle></math> from both sides of the equation.

Multiply each term in <math><mstyle displaystyle="true"><mo>-</mo><mi>x</mi><mo>=</mo><mo>-</mo><mn>12</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math>

Multiply each term in <math><mstyle displaystyle="true"><mo>-</mo><mi>x</mi><mo>=</mo><mo>-</mo><mn>12</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mrow><mo>(</mo><mo>-</mo><mi>x</mi><mo>)</mo></mrow><mo>⋅</mo><mo>-</mo><mn>1</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>12</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

The vertical asymptote occurs at <math><mstyle displaystyle="true"><mi>x</mi><mo>=</mo><mn>12</mn></mstyle></math> .

Vertical Asymptote: <math><mstyle displaystyle="true"><mi>x</mi><mo>=</mo><mn>12</mn></mstyle></math>

Vertical Asymptote: <math><mstyle displaystyle="true"><mi>x</mi><mo>=</mo><mn>12</mn></mstyle></math>

Replace the variable <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> with <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> in the expression.

Simplify the result.

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>11</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>12</mn></mstyle></math> .

Logarithm base <math><mstyle displaystyle="true"><mn>10</mn></mstyle></math> of <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> is <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

The final answer is <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

Convert <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> to decimal.

Replace the variable <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> with <math><mstyle displaystyle="true"><mn>10</mn></mstyle></math> in the expression.

Simplify the result.

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>10</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>10</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>12</mn></mstyle></math> .

The final answer is <math><mstyle displaystyle="true"><mi>log</mi><mrow><mo>(</mo><mn>2</mn><mo>)</mo></mrow></mstyle></math> .

Convert <math><mstyle displaystyle="true"><mi>log</mi><mrow><mo>(</mo><mn>2</mn><mo>)</mo></mrow></mstyle></math> to decimal.

Replace the variable <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> with <math><mstyle displaystyle="true"><mn>9</mn></mstyle></math> in the expression.

Simplify the result.

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>9</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>9</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>12</mn></mstyle></math> .

The final answer is <math><mstyle displaystyle="true"><mi>log</mi><mrow><mo>(</mo><mn>3</mn><mo>)</mo></mrow></mstyle></math> .

Convert <math><mstyle displaystyle="true"><mi>log</mi><mrow><mo>(</mo><mn>3</mn><mo>)</mo></mrow></mstyle></math> to decimal.

The log function can be graphed using the vertical asymptote at <math><mstyle displaystyle="true"><mi>x</mi><mo>=</mo><mn>12</mn></mstyle></math> and the points <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>11</mn><mo>,</mo><mn>0</mn><mo>)</mo></mrow><mo>,</mo><mrow><mo>(</mo><mn>10</mn><mo>,</mo><mn>0.30102999</mn><mo>)</mo></mrow><mo>,</mo><mrow><mo>(</mo><mn>9</mn><mo>,</mo><mn>0.47712125</mn><mo>)</mo></mrow></mstyle></math> .

Vertical Asymptote: <math><mstyle displaystyle="true"><mi>x</mi><mo>=</mo><mn>12</mn></mstyle></math>

Do you know how to Graph f(x) = log of 12-x? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.

Name | one billion three hundred sixty-nine million seven hundred eleven thousand four hundred thirty-six |
---|

- 1369711436 has 64 divisors, whose sum is
**3304294560** - The reverse of 1369711436 is
**6341179631** - Previous prime number is
**53**

- Is Prime? no
- Number parity even
- Number length 10
- Sum of Digits 41
- Digital Root 5

Name | one billion four million seven hundred fifty-two thousand five hundred sixty-eight |
---|

- 1004752568 has 16 divisors, whose sum is
**3391039944** - The reverse of 1004752568 is
**8652574001** - Previous prime number is
**2**

- Is Prime? no
- Number parity even
- Number length 10
- Sum of Digits 38
- Digital Root 2

Name | one billion three hundred fifty-three million one hundred sixty-nine thousand eight hundred eighty-three |
---|

- 1353169883 has 16 divisors, whose sum is
**1499856960** - The reverse of 1353169883 is
**3889613531** - Previous prime number is
**37**

- Is Prime? no
- Number parity odd
- Number length 10
- Sum of Digits 47
- Digital Root 2